The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/bit.10906
|View full text |Cite
|
Sign up to set email alerts
|

Optimized procedure for renaturation of recombinant human bone morphogenetic protein‐2 at high protein concentration

Abstract: The human gene encoding the mature form of bone morphogenetic protein-2 (hBMP-2), a dimeric disulfide-bonded protein of the cystine knot growth factor family, was expressed in recombinant Escherichia coli using a temperature-inducible expression system. The recombinant protein was produced in the form of cytoplasmic inclusion bodies and the effect of different variables on the renaturation of rhBMP-2 was investigated. In particular, variables such as pH, redox conditions, protein concentration, temperature, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 32 publications
2
62
0
Order By: Relevance
“…In addition, we showed that acidic pH either dissociates the BMP-7 complex or subjects it to gross conformational changes. Refolding experiments of growth factor domains of other TGF␤ superfamily members have demonstrated the need for harsh denaturants and aggregation suppressors (28) and have suggested that a principal function of the prodomain may be to solubilize the growth factor dimer by shielding the pronounced hydrophobic surfaces present on the mature were separated by SDS-PAGE with (ϩ) or without (Ϫ) disulfide bond reducing agent and transferred to nitrocellulose paper. Anti-histidine (anti-HIS), mAb 2, and mAb 33 immunoblot the prodomain of BMP-7 (ૺ).…”
Section: Figmentioning
confidence: 99%
“…In addition, we showed that acidic pH either dissociates the BMP-7 complex or subjects it to gross conformational changes. Refolding experiments of growth factor domains of other TGF␤ superfamily members have demonstrated the need for harsh denaturants and aggregation suppressors (28) and have suggested that a principal function of the prodomain may be to solubilize the growth factor dimer by shielding the pronounced hydrophobic surfaces present on the mature were separated by SDS-PAGE with (ϩ) or without (Ϫ) disulfide bond reducing agent and transferred to nitrocellulose paper. Anti-histidine (anti-HIS), mAb 2, and mAb 33 immunoblot the prodomain of BMP-7 (ૺ).…”
Section: Figmentioning
confidence: 99%
“…The method of producing active rhBMP-2 was well explored, 26,34 and was used in our experiments with slight modification. The fused (His) 6 tag could facilitate the protein purification and provide a simple detective method for the protein in the collagen binding assay.…”
Section: Discussionmentioning
confidence: 99%
“…The two genes were cloned from PCR products, inserted into a high-performance bacterial expression vector pET-28a (Novagen), and transformed into the BL21 (DE3) strain of E. coli. Proteins were prepared as described 26,34 with slight modification. Briefly, the proteins expression was induced with 1 mM isopropyl b-D-thiogalactopyranoside (IPTG) at 378C for 4 h. The recombinant fusion protein was isolated from Escherichia coli as inclusion bodies by sonication and centrifugation, and then dissolved with 8M urea and purified using nickel chelate chromatography (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations